Coastal Evolution and Relative Sea Level Changes at Psatha (Alkyonides Bay, Greece) - Anna Karkani; Niki Evelpidou; Giannis Saitis; Konstantinos Tsanakas; Hara Drinia; Emmanuel Vassilakis; Efthimios Karymbalis; Dimitrios-Vasileios Batzakis (Journal of Marine Science and Engineering, 2023)
Geomorphological and sedimentological indicators are often used to reconstruct not only coastal evolution, but also relative sea level changes. In this work, we studied the coastal sediments of Psatha bay (Alkyonides Gulf, Greece) and beachrock outcrops in order to reconstruct the coastal evolution of the area. The drillings analysis included stratigraphy, sediment texture and radiocarbon dating. Detailed mapping of the beachrocks was accomplished using DGPS-GNSS, as well as mineralogical analysis and OSL dating of beachrock samples. The new beachrock index points indicate a sea level that fell by 0.64 ± 0.13 m since 2200 ± 210 years BP and by 0.95 ± 0.13 m since 4160 ± 320 years BP, as a direct result of its location near the uplifting footwall of Psatha fault, suggesting further a rate of tectonic uplift of ~0.26 mm/yr for the late Holocene.